Đánh giá kinh tế địa chất các mỏ nhỏ dầu khí - Tùng, Đỗ Hữu (Vietnam Journal of Earth Sciences, 2005)
At present, most of produced petroleum fields have reserve dozens of million tons of oil, dozens of billion m3 of gas. To design production, these fields must be seriously and carefully evaluated in terms of economics and geology aspects, otherwise risks will be high. With fields have reserve up to 10 million tons of oil, 10 billion m3 of gas, which are considered small fields , are not or a litter economic effective when production. These discoveries are usually returned to the state from contractors. There fore, producing petroleum small fields effectively is sensitive matter, is attention of many countries, but it is not easy. Making necessary regulars to develop petroleum small fields production has important meaning to economy.